Immunomodulatory effects of pidotimod in adults with community-acquired pneumonia undergoing standard antibiotic therapy. (June 2017) - Trabattoni, D.; Clerici, M.; Centanni, S.; Mantero, M.; Garziano, M.; Blasi, F.
Abstract: The morbidity and mortality of community-acquired pneumonia (CAP) are still elevated and two aspects seem to contribute to a worse outcome: an uncontrolled inflammatory reaction and an inadequate immune response. Adjuvants, including corticosteroids and intravenous immunoglobulins, have been proposed to counterbalance these effects but their efficacy is only partial. We examined the immunomodulatory activity of Pidotimod (PDT), a synthetic dipeptide molecule in adult patients hospitalized for CAP. Sixteen patients with a diagnosis of CAP and a PSI score III or IV and/or a CURB-65 0–2 were randomized to receive either levofloxacin 500 mg b.i.d. alone or levofloxacin plus PDT (800mg, 2 daily doses). Blood samples were drawn at baseline (T0), before initiation of therapy, as well as 3 (T3), and 5 (T5) days after initiation of therapy. Immunologic and clinical parameters were analyzed at each time point. Supplementation of antibiotic therapy with PDT resulted in an upregulation of antimicrobial and of immunomodulatory proteins as well as in an increased percentage of Toll like receptor (TLR)2- and TLR4, and of CD80- and CD86-expressing immune cells. Notably, Pidotimod supplementation was also associated with a robust reduction of TNFα-producing immune cells. No significant differences were observed in clinical parameters. These results confirm that supplementation of antibiotic therapy with Pidotimod in patients with CAP results in a potentially beneficial modulation of innate immunity.